2001
DOI: 10.1104/pp.010372
|View full text |Cite
|
Sign up to set email alerts
|

An Off-Line Implementation of the Stable Isotope Technique for Measurements of Alternative Respiratory Pathway Activities

Abstract: In situ measurements of alternative respiratory pathway activity are needed to provide insight into the energy efficiency of plant metabolism under various conditions in the field. The only reliable method at present to measure alternative oxidase (AOX) activity is through measurement of changes in ␦ 18 O(O 2 ), which to date has only been used in laboratory environments. We have developed a cuvette system to measure partitioning of electrons to AOX that is suitable for off-line use and for field experiments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…This was especially evident in cold transferred plants, where COX activity declined whilst AOX activity increased significantly. This switching between the AOX and COX pathways is well documented in a range of species such as Alocasia odora, Spinacia oleracea, Zea mays and Phaseolus vulgaris (Ribas-Carbo et al 2000;Nagel et al 2001;Nogochi et al 2001) and have been confirmed in our recent study involving poplar (Ow et al 2008). Furthermore, the AOX pathway is highly sensitive to changes in temperature and engagement of this pathway may have advantages for plant acclimation to colder temperature, whereby energy that should otherwise be conserved as ATP is converted to heat (Ribas-Carbo et al 2000).…”
Section: Respiratory Responses To Changes In Temperaturesupporting
confidence: 75%
“…This was especially evident in cold transferred plants, where COX activity declined whilst AOX activity increased significantly. This switching between the AOX and COX pathways is well documented in a range of species such as Alocasia odora, Spinacia oleracea, Zea mays and Phaseolus vulgaris (Ribas-Carbo et al 2000;Nagel et al 2001;Nogochi et al 2001) and have been confirmed in our recent study involving poplar (Ow et al 2008). Furthermore, the AOX pathway is highly sensitive to changes in temperature and engagement of this pathway may have advantages for plant acclimation to colder temperature, whereby energy that should otherwise be conserved as ATP is converted to heat (Ribas-Carbo et al 2000).…”
Section: Respiratory Responses To Changes In Temperaturesupporting
confidence: 75%
“…Changes in electron partitioning through the two terminal oxidase pathways in respiration were assessed in vivo based on the premise that the CP and the AP discriminate against the heavier isotope of oxygen ( 18 O) to different extents (Guy et al 1989, Ribas‐Carbo et al 2005a). We adopted an ‘off‐line’ method modified from that of Nagel et al (2001) that has been described previously (Searle et al in press). Leaves were cut in half before being placed in 12 ml Exetainers (Labco, High Wycombe, Buckinghamshire, UK).…”
Section: Methodsmentioning
confidence: 99%
“…1989; Ribas‐Carbo, Robinson & Giles 2005a). We adopted an ‘off‐line’ method modified from that of Nagel, Waldron & Jones (2001) that has been previously described (Searle et al. 2011a).…”
Section: Methodsmentioning
confidence: 99%